2016
DOI: 10.17675/2305-6894-2016-5-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Organic corrosion inhibitors: where are we now? A review. Part II. Passivation and the role of chemical structure of carboxylates

Abstract: This article provides an overview of works (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) devoted to the passivation of various metals and the influence of organic carboxylic acids and their salts thereon. The results of corrosion and electrochemical studies, as well studies on the composition and structural features of surface layers on the metals being protected by a variety of physicochemical methods are considered. Protection of metals by organic corrosion inhibitors (CIs) is based mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 54 publications
(110 reference statements)
2
50
0
Order By: Relevance
“…In the second part of this review [14], a similar situation observed by Japanese researchers was already discussed when comparing the adsorption of mono-and α,ω-dicarboxylates on iron. On the other hand, if just one phosphonic group serves as the "anchor" group, the terminal second hydrophilic phosphonic group prevents the surface hydrophobization and remains free to form complexes with the metal cations present in the solution, including Fe n+ .…”
Section: Mono-and Diphosphonic Acids and Their Saltssupporting
confidence: 61%
See 4 more Smart Citations
“…In the second part of this review [14], a similar situation observed by Japanese researchers was already discussed when comparing the adsorption of mono-and α,ω-dicarboxylates on iron. On the other hand, if just one phosphonic group serves as the "anchor" group, the terminal second hydrophilic phosphonic group prevents the surface hydrophobization and remains free to form complexes with the metal cations present in the solution, including Fe n+ .…”
Section: Mono-and Diphosphonic Acids and Their Saltssupporting
confidence: 61%
“…In the first case, the delay of the potential characteristic of iron oxide reduction was observed on the E = f() curve, whereas it was completely absent in the second case ( Figure 4). This fact allowed the authors to assume that APhC 12 is able to protect St3 by the "nonoxide passivation" mechanism in a manner similar to that previously proved for the anions of certain higher carboxylic acids [4,14]. Chronopotentiograms of St3 steel in deaerated borate buffer solution with pH 7.3 at cathodic polarization, i = 10 μA/cm 2 , after passivation of the electrode: 1 -by anodic polarization in borate buffer to E = 0.2 V; 2 -same, but with an exposure time of 10 min at E = 0.2 V; 3 -by anodic polarization, but with preliminary cathodic activation in the presence of 5 mM APhC 12 rather that in the pure buffer [19].…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 61%
See 3 more Smart Citations